If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-2x-1=-4
We simplify the equation to the form, which is simple to understand
-2x-1=-4
We move all terms containing x to the left and all other terms to the right.
-2x=-4+1
We simplify left and right side of the equation.
-2x=-3
We divide both sides of the equation by -2 to get x.
x=1.5
| a/6=25 | | 24-12-(-14)=x | | P-8=12-3p | | 4p+1000000=12600000 | | ln(x+1)+ln(x+1)=2 | | g-9=-2g+6 | | -7/3/3/4 | | 10b+4=3B+16 | | .6x^2-18x-2=0 | | -8x-5=2x+7 | | 4p+1000000=12000000 | | -3+4x=22 | | -12-4x=4(-3x+5) | | 4x^3-21x^2-18x=0 | | 3ab(2x-y)-5a^2(y-2x)=0 | | -6x+10=4x-30 | | x-1/4=1/3 | | 8.17=a+0.03+a | | 3x-7x=6(x-3)-2(6x+3) | | -6x+10=4x | | 9-12/x=-3 | | 5x^2+30x+89=124 | | 5x-4=8+4x | | 6p-15p+12-32= | | 24.95+5.95s= | | -9/5/8 | | 17-3x/6=1/2x-4 | | Y=40X-8 | | 6+7*5+8=73 | | 5(7x+2)= | | 2cos^2(2x+5)=1 | | 24.1g-35.75=6.9g+587.72 |